Perlindungan Hukum Bagi Pihak Yang Dirugikan Akibat Terjadinya Persekongkolan Tender - Iqbal, Muhammad; Syam, Misnar; Yasniwati, Yasniwati (Dinasti Research, 2025)
Opportunities for government infrastructure development require procurement of goods and services, the regulation of procurement of goods and services is regulated in Presidential Regulation (Perpres) Number 12 of 2021 concerning Government Procurement of Goods and Services. In this opportunity for procurement of goods and services, the government has an opportunity for a tender process, in tender procurement sometimes a tender conspiracy arises. This tender conspiracy is regulated in Article 22 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. In Case Number 08/KPPU-L/2023 and Case Number 17/KPPU-L/2022, there has been a tender conspiracy that has harmed job owners, business actors and the community. Problem Formulation (1) What is the legal protection for parties who are harmed due to tender conspiracy in the procurement of goods and services? (2) What are the indications of tender conspiracy in the hearing of the Business Competition Supervisory Commission? The research method used is Normative Jurisprudential, the type of data used is secondary data, to obtain secondary data, primary legal material data sources and secondary legal materials are used, data collection techniques are literature studies and interviews, qualitative analysis data analysis techniques. The results of the study (1) the form of protection provided to the injured parties in Case Number 08/KPPU-L/2023 and Case Number 17/KPPU-L/2022, namely providing protection by imposing large fines and hoping to provide a deterrent effect on business actors (Reported). (2) The indications contained in Case Number 08/KPPU-L/2023 and Case Number 17/KPPU-L/2022 are that there are indications that several participants are involved in one control, which can be seen from the similarity of the technical documents they submit. In addition, there is suspicion of collusion during the implementation and evaluation process, including, the tender winner who subcontracts the work to another company or the losing tender participant. At the evaluation and determination stage of the tender winner, there were also indications that the committee tended to give privileges to certain participants. Furthermore, when submitting objections, the committee did not seem to respond to complaints from tender participants, which further strengthened the suspicion of collusion.